Reaction of white guinea yam (Dioscorea rotundata Poir.) genotypes to virus diseases in four agroecological zones in Nigeria - Odu, B.O.; Asiedu, Robert; Shoyinka, S.A.; Hughes, J.D. (Wiley, 2006)
Nineteen white yam (Dioscorea rotundata Poir.) genotypes were grown in four agroecological zones in Nigeria for 2 years to study their responses to yam virus diseases, and to investigate the influence of genotype × environment (G × E) interactions on their reactions to virus infection, using the Additive Main Effects and Multiplicative Interactions (AMMI) Statistical Model. Environments, genotypes and G × E interactions were all highly significant (P < 0.0001) for the virus diseases. The G × E interactions accounted for 21.4% of the treatment sum of squares, and influenced the relative ranking of the genotypes across the eight environments. Genotypes TDr 93-32 and TDr 93-27 were identified as the most stable genotypes, while TDr 1621 and TDr 1640 were shown to have resistance to virus diseases. The study also identified Jos with high yam virus disease severity as the most appropriate site for the screening of D. rotundata genotypes.